Analysis of patient flow and barriers to timely discharge from general medical wards at a tertiary academic hospital in Cape Town, South Africa - Mehreen Hunter; Shrikant Peters; Nontuthuko Khumalo; Mary-Ann Davies (BMC, 2024)
Abstract Background Movement of patients through a health establishment is a complex activity reliant upon multi-actor co-ordination across departments. The challenge of enhancing service delivery to meet the needs of a growing and aging population, whilst minimizing expense, is a global concern. There is an urgent need to understand and quantify systemic gaps in the efficient delivery of healthcare services. Stagnation of patient flow has negative impacts on both staff and patients by increasing risks of adverse outcomes, staff frustration and job dissatisfaction. An inefficient discharge process can be a significant barrier to timely patient movement. Methods A retrospective cohort study was conducted at a tertiary, academic hospital in the Western Cape, South Africa to assess the journey of medical patients from admission to discharge across the five different medical teams (firms) within the general medicine department. Consecutive sampling was used to capture all eligible adult medical in-patients admitted from the emergency department (ED) to general medicine from the 11th - 20th April 2023 and discharged up until the 30th of April 2023. We reviewed the patient notes (folders) of these individuals using a data-extraction tool to ascertain reasons for admission and barriers to timely discharge. Results Among 86 patient folders reviewed, cumulatively accounting for 596 in-patient days, a difference in the median length of in-patient stay between medical firms (p = 0.042) was noted. The shortest length of stay corresponded to firms with the greatest proportion of daily senior staff oversight (defined as documented patient reviews by a registrar, medical officer and/or consultant independently or in addition to reviews done for the day by interns and/or students). While 52% of patients vacated their beds between 14:00 and 17:00, 66% of patients were admitted after 20:00. Reasons for prolonged admission were variable, and attributable to a range of different disciplines across the multidisciplinary team. Conclusion Whilst this study did not evaluate the appropriateness of chosen medical management but rather systemic drivers affecting patient movement and barriers to timely discharge, the delays in discharge were noted to be multi-factorial including facets across the efficient delivery of medical care, availability of resources and the internal operational frameworks for the institution. Understanding the need to optimize internal process efficiencies with regards to prompt acquisition of investigations, improvement of senior staff oversight and the creation of a standardized discharge process, could enhance efficient patient movement.